"Michael addition" reaction onto vinyl sulfonyl(trifluoromethylsulfonyl)imide: An easy access to sulfonyl(trifluoromethylsulfonyl)imide-based monomers and polymers. (October 2018) - Ho, Hien The; Rollet, Marion; Phan, Trang N.T.; Gigmes, Didier
Graphical abstract: Highlights: Synthesis of STFSI-functionalized monomers by using "Michael-addition" onto vinyl-STFSI. Efficient addition of diallylamine, dipropargylamine, dimethylmalonate and diethylmalonate onto vinyl-STFSI. Synthesis of STFSI-based polymers via step-growth polymerization technique. Abstract: Sulfonyl(trifluoromethylsulfonyl) imide anion (STFSI, SO2 N (−) SO2 CF3 ) is one of the most important sulfonimide groups for organic and material synthesis. However, the synthesis of STFSI-functionalized monomers and related polymers is still a problematic issue, comprising multi-step and complex synthetic processes. To overcome this drawback, we developed a robust and versatile strategy to prepare original STFSI-based monomers using the "Michael addition" reaction conducted in the presence of vinyl sulfonyl(trifluoromethylsulfonyl)imide and either an amine or a malonate derivative. Furthermore, the synthesized monomers were used to prepare the corresponding STFSI-functionalized polymers using step-growth polymerization with potential applications as electrolytes.